PENGETAHUAN LOKAL IKAN CEMPEDIK (Osteochilus spilurus) DI KECAMATAN MEMBALONG, BELITUNG - Ardiansyah Kurniawan; Andri Kurniawan; Yulian Fakhrurrozi; Fenny Widyanthi; Jeny Setiawan; Kartika Kartika; Sartili Sartili; Neri Rizkika; Tio Arezki (Jurusan Akuakultur, Universitas Bangka Belitung, 2020)
Cempedik fish (Osteochilus spilurus) has an important economic value in East Belitung. Still, its trade has not been identified in the Belitung Regency, which is in the western part of Belitung Island. Belitung community perceptions related to fish catching, consumption, and understanding of this fish need to be known to complement the results of studies in East Belitung. Techniques of data collection were carried out using structured interviews in the Membalong District, which has 55% of the Belitung Regency river. The community responses were compared with secondary data of East Belitung citizens. The majority of respondents said that they knew and consumed Cempedik Fish, knew their fishing season and fishing gear, and were optimistic about their cultivation potential. The majority of respondent say knows, consumes, knows the fishing season and fishing gear, and optimistic for the potential farming of Cempedik fish. Most of the Cempedik fish consumption is obtained from catching in the river. Fishing season of Cempedik fish occurs in the dry season, with the majority of fishing gear used are nets. The difference in fishing season and economic value with East Belitung provides opportunities for fish distribution to meet market needs.